Acute dosing of latrepirdine (Dimebon™), a possible Alzheimer therapeutic, elevates extracellular amyloid-β levels in vitro and in vivo - Steele, John W (BioMed Central, 2009)
BACKGROUND: Recent reports suggest that latrepirdine (Dimebon™, dimebolin), a retired Russian antihistamine, improves cognitive function in aged rodents and in patients with mild to moderate Alzheimer's disease (AD). However, the mechanism(s) underlying this benefit remain elusive. AD is characterized by extracellular accumulation of the amyloid-β (Aβ) peptide in the brain, and Aβ-lowering drugs are currently among the most popular anti-amyloid agents under development for the treatment of AD. In the current study, we assessed the effect of acute dosing of latrepirdine on levels of extracellular Aβ using in vitro and in vivo experimental systems. RESULTS: We evaluated extracellular levels of Aβ in three experimental systems, under basal conditions and after treatment with latrepirdine. Mouse N2a neuroblastoma cells overexpressing Swedish APP were incubated for 6 hr in the presence of either vehicle or vehicle + latrepirdine (500pM-5 μM). Synaptoneurosomes were isolated from TgCRND8 mutant APP-overexpressing transgenic mice and incubated for 0 to 10 min in the absence or presence of latrepirdine (1 μM or 10 μM). Drug-naïve Tg2576 Swedish mutant APP overexpressing transgenic mice received a single intraperitoneal injection of either vehicle or vehicle + latrepirdine (3.5 mg/kg). Picomolar to nanomolar concentrations of acutely administered latrepirdine increased the extracellular concentration of Aβ in the conditioned media from Swedish mutant APP-overexpressing N2a cells by up to 64% (p = 0.01), while a clinically relevant acute dose of latrepirdine administered i.p. led to an increase in the interstitial fluid of freely moving APP transgenic mice by up to 40% (p = 0.01). Reconstitution of membrane protein trafficking and processing is frequently inefficient, and, consistent with this interpretation, latrepirdine treatment of isolated TgCRND8 synaptoneurosomes involved higher concentrations of drug (1-10 μM) and led to more modest increases in extracellular Aβ(x-42 )levels (+10%; p = 0.001); of note, however, was the observation that extracellular Aβ(x-40 )levels did not change. CONCLUSIONS: Here, we report the surprising association of acute latrepirdine dosing with elevated levels of extracellular Aβ as measured in three independent neuron-related or neuron-derived systems, including the hippocampus of freely moving Tg2576 mice. Given the reported association of chronic latrepirdine treatment with improvement in cognitive function, the effects of chronic latrepirdine treatment on extracellular Aβ levels must now be determined.